Flintridge Foundation Awards for Visual Artists 1999/2000. - Conkelton, Sheryl; Cook, Lia; Gamblin, Noriko; Gamboa Jr., Harry; Hall, Doug; Lacy, Suzanne; Levi Strauss, David; Martinez, Daniel Joseph; McMillen, Michael C.; Moseley, Alexander; Noriega, Chon A.; Pittman, Lari; et al. (Pasadena : Flintridge Foundation Pasadena, 2000)
Cook, Lia ; Gamboa Jr., Harry ; Hall, Doug ; Kos, Paul ; Lacy, Suzanne ; Martinez, Daniel Joseph ; McMillen, Michael C. ; Pittman, Lari ; Saar, Alison ; Shelton, Peter ; Simpson, Buster ; Sultan, Larry
biog., tent., prijzen, coll., bibliog. p. 56-61
This book is published on the occasion of the second biennial cycle of the Flintridge Foundation Awards for Visual Artists.
Engels
boek